The Role of Sanggar Madu Mulyo in Preserving Music Culture in Sidoarjo: The Role of Sanggar Madu Mulyo in Preserving Music Culture in Sidoarjo - febriana, dina; Juwariyah, Anik (Solah, 2025)
Campursari is a form of traditional Javanese music art that combines elements of gamelan with modern instruments. Sanggar Madu Mulyo in Sidoarjo is an important place to preserve this art, not only through regular performances at various cultural events, but also through training the younger generation and performance innovation. Through a qualitative descriptive approach with observation, interviews, and documentation, this study found that although Sanggar Madu Mulyo faces challenges in the form of minimal interest from the younger generation, limited funds, and lack of public appreciation, their role remains important in maintaining the sustainability of traditional Javanese culture. Cross-sector collaboration and innovation are needed to keep Campursari alive in the modern era